The audio code of the novel by Guy de Maupassant “Strong like Death” (“Fort comme la mort”) - Мурадова, Ирина Робертовна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article is devoted to the analysis of the audio poetics of the novel by G. de Maupassant “Strong like Death”. It is established that the mimetic musical ecphrasis (verbal descriptions and references to the works of J. Haydn, R. Schumann, F. Schubert, S. Gounod) – monological, complete and incomplete, discrete – perform the characterological, expressive, emotional and plot-compositional functions in the novel, creating an inner plot of the nuanced psychic life of the protagonist. The problems of the novel are embodied in non-musical audio ways (first and foremost, it is an alarming striking of the clock).